The Portrayal of Women in Advertising - Pallavi Soni (International Journal of Engineering and Management Research, 2020)
The portrayal of women in media advertisements, over the decades, has been about unrealistic body images, sexual objectification, physical beauty, and family roles. These advertisements affect the self-esteem and confidence of the female viewers and results in dissatisfaction and pressure to conform to certain body norms. It also affects the way women are perceived and sets men’s expectations of a woman’s appearance. A study was conducted on 313 respondents to understand the effects of such advertisements. It was observed that advertisements showing unrealistic body images of women pressurized them to conform to body norms. It was also observed that these advertisements affect the way women are accepted in the society. Men’s perception of women and their expectations of women’s appearance are also affected in the process. Majority of the respondents agreed that they would like to see more reality-based images in today’s advertisements.